Complete blood count in neonatal Intensive care Unit (NICU): Performance comparison between POCT Sight OLO® and Sysmex XN-9100™ hematology analyzers - Francesca Nencini; Alessandro Bonari; Sara Ciullini Mannurita; Alessandra Mongia; Francesca Romano; Maria Garieri; Edda Russo; Silvia Sastrucci; Graziella Marrani; Martina Tonelli; Stefano Salti; Niccola Funel; et al. (Practical Laboratory Medicine)
Background and aims: The use of a POCT (Point Of Care Test) could help in reducing the impact of pre-analytical errors in particular in challenging newborn samples.The study purpose is to compare the POCT Sight OLO® hematology analyzer, validated for >3 months patients, with the reference system Sysmex XN-9100™ in Neonatal Intensive Care Unit (NICU). Material and methods: The two analyzers were compared through Passing-Bablok regression analysis and Bland-Altman plot. Results: We analyzed 65 blood samples, in detail 38 from adults and 27 from newborns.The regression analysis results performed in the newborn and adult patients showed a good agreement between the two instruments. The evaluation of the Bland-Altman plots showed comparable values of bias <10 % for the most of parameters.The evaluation of sample flags for the presence of distributional and morphological abnormalities showed a partial accordance between the two approaches, but the POCT exhibited good performance compared to the final report revised by the laboratory specialist. Conclusions: The comparison of the two instruments demonstrated that they provide comparable blood counts, also in patients aged <3 months. The POCT allows having reliable analytical data and faster turning around time, particularly useful in NICU.